IPOMOEA BATATAS SYRUP DECREASE MALONDIALDEHYDE AND INCREASE NITROUS OXIDE PLASMA LEVELS AMONGST MODERATE SMOKER WORKERS AT DENPASAR - Dwi-Primayanti, I D. A. I.; Aman, I G. M.; Agus-Bagiada, N. (BALI MEDICAL JOURNAL, 2013)
Objective: Cells and tissues are continuously damaged by reactive oxygen species. Cigarette smoke is one of an exogenous source of free radical containing more than 4000 chemical compounds, that triggering the formation of free radicals related to diseases and aging process. Anthocyanins are potent antioxidants that are widely distributed in fruit, vegetables, red wines and Ipomea batatas. The aim of this study was to determine the effect of Ipomea batatas as a source of antioxidants in decreasing levels of malondialdehyde (MDA) and increasing of Nitrous oxide (nitrite/nitrate/NO x ) plasma in moderate smokers of workers at Denpasar. Method : This was an experimental study with a pretest-posttest control groups design. There are 33 moderate smokers who were divided into three groups, control group (placebo), treatment group with 15 ml purple sweet potato syrup (P1) and 30 ml (P2), for 14 days. All groups were performed the laboratory examinations for MDA and NOx plasma before and after the treatment. Results : This study showed that there were significant differences ( p <0.05) both in MDA and NOx plasma levels in the control group, P1 and P2. The decrease of MDA levels on P1 was 35.39% and on P2 was 49.87%. The increase of NOx plasma levels was 7.78% for P1 and 14.68% for P2. Conclusion: From this study, it can be concluded that Ipomea batatas syrup contains of 8mg/mL anthocyanins, probably play a role in reducing the free radical and thus reducing the risk of disease and slowing the aging process.
Keywords: syrup purple sweet potato, anthocyanins, oxidative stress, moderate smoker